2014
DOI: 10.1037/xge0000016
|View full text |Cite
|
Sign up to set email alerts
|

Memories of traumatic events in childhood fade after experiencing similar less stressful events: Results from two natural experiments.

Abstract: The long-term stability of youth reports of traumatic events is largely unknown. Translational animal research suggests that there may be an alteration of memories for traumatic events via memory reconsolidation processes, whereas clinical research suggests memory alteration may occur through augmentation by negative emotions. In this report, 2 natural experiments test reconsolidation model and augmentation model predictions about the course of traumatic memories in youth. Data are from 2 prospective studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…While cumulatively increased exposure to damage and illness increased poor mental health outcomes, age at first disaster remained protective. A possible explanation for this is that early initial exposure may better equip a person for coping during later disasters, leading to reduced long-term effects, especially when later disasters are perceived as being less severe than earlier exposures (Harville et al 2011; Weems et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While cumulatively increased exposure to damage and illness increased poor mental health outcomes, age at first disaster remained protective. A possible explanation for this is that early initial exposure may better equip a person for coping during later disasters, leading to reduced long-term effects, especially when later disasters are perceived as being less severe than earlier exposures (Harville et al 2011; Weems et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, since the data was collected years after the disasters, it cannot be ascertained whether reported exposures were influenced by the respondent’s mental health at the time of the interview, although age at the time of the interview would not be subject to reporting bias. In spite of this, a study among youth exposed to Hurricanes Katrina and Gustav found relatively high stability in reports of exposure to Katrina years following the disaster among children who had high Gustav exposure, whereas reports decreased among those with low Gustav exposure (Weems et al 2014). Thus, it is thought that reports of exposure should be fairly accurate overall, and, if anything, may be underreported among participants who had less stressful experiences in later disasters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The items were drawn from questionnaires administered in studies of Hurricane Ike (48) and Hurricane Katrina (49). Reports of hurricane-related experiences have previously been demonstrated to be stable across time (50). Eight items (life disrupted by hurricane, children fearing for safety, difficulty finding food or warmth, difficulty finding gasoline, children complaining more than usual, damage to home or possessions, family’s safety threatened, and financial hardship) were rated on a 5-point scale (1 = not at all affected; 5 = extremely affected).…”
Section: Methodsmentioning
confidence: 99%
“…This set of studies may provide a highly simplified but valid laboratory model of real-life traumatic events such as Hurricane Katrina (Figure 1). Based on the reconsolidation theory, Weems et al (1) predicted that exposure to a milder hurricane would alleviate the negative consequences of Hurricane Katrina. As expected, they found that youth with high exposure to Hurricane Katrina but low exposure to Hurricane Gustav retrieved fewer Katrina-related negative memories (1) and exhibited reduced posttraumatic stress disorder symptoms (2).…”
mentioning
confidence: 99%